The Impact of Burnout on Organizational Productivity and Sustainability - Junaidi, Junaidi; Anwar, Haeril (Indonesian Journal of Research and Service Studies, 2024)
Burnout has become a major challenge in human resource management due to its potential to reduce work productivity and hinder organizational sustainability. This study aims to comprehensively analyze the impact of burnout on productivity and its implications for organizational sustainability through a synthesis of various previous research findings. The study employed a literature review method, examining reputable scientific articles, academic books, and relevant official documents, then analyzed using content analysis and narrative synthesis approaches. The results indicate that burnout contributes to decreased productivity through reduced work engagement, creativity, decision-making quality, and individual performance. This decreased productivity subsequently impacts organizational sustainability through weakened innovation, increased human resource attrition, and reduced organizational ability to adapt to change. This study confirms that burnout management needs to be an integral part of organizational strategies to increase productivity while supporting organizational sustainability.